Legal Analysis of Government Control Over the Company Subsidiaries in State-Owned Enterprises Holding - Alfian Syahri (Journal of Social Science, 2023)
State-owned enterprises (SOEs) are one of the business entities aiming to advance people’s wellbeing. Government Regulation (PP) No. 72 of 2016 concerning Procedures for Participation and Stock Capital Administration in State-Owned Enterprises and Limited Companies states that SOEs which are used as capital participation of other SOEs become subsidiaries of these other SOEs. It is considered to undermine the function of the The House of Representatives and make the state seem to have lost control of the former SOEs. The PP was tested materially because it was considered not in accordance with Law no. 19 of 2003 concerning SOEs. Based on the judicial review, the Supreme Court (MA) rejected the lawsuit. However , the Supreme Court’s consideration stated that SOEs which are SOEs subsidiaries remain state-owned and are inversely proportional to the Constitutional Court decision No.01/PHPU- PRES/XVII/2019 dated June 24, 2019, which in its consideration stated that SOEs must be considered the composition of its state-owned shares. The status of SOEs that has changed to become a SOEs subsidiary is no longer categorized as SOEs but becomes Limited Companies with special rights with a special assignment from the Government because it has series A shares (merah putih shares). The status of the State’s Wealth of the former SOEs becomes the assets of the former SOEs but still within the scope of State Finance.